2001
DOI: 10.1191/026921601668030190
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of episodic pain in cancer: a survey of hospice patients on admission

Abstract: Pain that varies with time, referred to here as episodic pain, is a commonly encountered but under-investigated clinical problem. Previous studies of cancer patients have found that a significant proportion of their pains are episodic. To establish the prevalence and characteristics of episodic pains in hospice in-patients we assessed 245 consecutive admissions to four hospices in Yorkshire. The admitting doctor completed a questionnaire, detailing the characteristics of all pains experienced by the patient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 15 publications
(20 reference statements)
0
46
0
4
Order By: Relevance
“…In some studies, peaks of pain intensity have been reported independently on the analgesic treatment, and in others no clear distinction between background and BTcP pain intensity has been reported [10][11][12][13][14]16,17 . We have previously shown that many studies of BTcP have been performed in patients with uncontrolled background pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, peaks of pain intensity have been reported independently on the analgesic treatment, and in others no clear distinction between background and BTcP pain intensity has been reported [10][11][12][13][14]16,17 . We have previously shown that many studies of BTcP have been performed in patients with uncontrolled background pain.…”
Section: Discussionmentioning
confidence: 99%
“…despite relatively stable and adequately controlled baseline pain'' 4,7,8 . Other authors have proposed that BTcP is a transient exacerbation of pain that occurs irrespective of basal analgesia 9 , episodes of pain occurring on an unrealistic pain-free background 10 , or ''any transient flare of pain subjectively distinguishable from an otherwise more or less stable background pain'' 11 . In some cases there was no operational definition a priori, with incident pain due to movement given as an example, even though patients could have their pain uncontrolled or were not receiving opioids 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, other definitions were proposed, such as Ba transient exacerbation of pain that occurs irrespective of basal analgesia^ [13], Bepisodes of pain occurring on an unrealistic pain-free background^ [14], or Bany transient flare of pain subjectively distinguishable from an otherwise more or less stable background pain^ [15].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…In der palliativmedizinischen Literatur werden Prävalenzen des Durchbruchschmerzes zwischen 23 [5] und 93% [23] aller Tumorpatienten berichtet, wobei sich im Durchschnitt der bisher publizierten Ergebnisse Anteile von ca. 60-70% schätzen lassen.…”
Section: Erfahrungen Von Tumorpatienten Mit Durchbruchschmerzen Und Munclassified